2014
DOI: 10.1373/clinchem.2013.212035
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Atrioventricular Heart Block

Abstract: CASE DESCRIPTIONAs part of routine prenatal care, the obstetrician of a 25-year-old gravida 1, para 0 woman performed fetal heart-rate monitoring at 22 weeks gestational age. The fetal heart rate was 90 bpm, below the expected range of 120 -160 bpm. This finding prompted a subsequent fetal ultrasound and echocardiogram.The ultrasound exam showed no evidence of hydrops. Cardiac anatomy was normal, with 4 appropriately sized chambers, no valvular defects, and no abnormal communications between the right and left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…9 The antibody may be transferred at any time in gestation, 10 initiating its placental passage 12 weeks, the period of greatest vulnerability ranges from 16 and 24 weeks generally having a peak in antibody concentration, which explains the fact that over 80% of cases of congenital AV block are diagnosed before week 30. 4,10 The prognosis when associated with congenital heart disease is unfavorable, reaching a mortality rate of 50-80% in the 1st year of life, being left atrial isomerism malformation that confers higher mortality. 11 This contrasts with blocking immunologically whose intrauterine mortality is 6%, 16-19% overall mortality and when associated with endocardial fibroelastosis of 69%, requiring the use of pacemakers up to 70% of cases during the first 10 years of life.…”
Section: Induction Of Apoptosis In Myocytes and Cardiac Conduction Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The antibody may be transferred at any time in gestation, 10 initiating its placental passage 12 weeks, the period of greatest vulnerability ranges from 16 and 24 weeks generally having a peak in antibody concentration, which explains the fact that over 80% of cases of congenital AV block are diagnosed before week 30. 4,10 The prognosis when associated with congenital heart disease is unfavorable, reaching a mortality rate of 50-80% in the 1st year of life, being left atrial isomerism malformation that confers higher mortality. 11 This contrasts with blocking immunologically whose intrauterine mortality is 6%, 16-19% overall mortality and when associated with endocardial fibroelastosis of 69%, requiring the use of pacemakers up to 70% of cases during the first 10 years of life.…”
Section: Induction Of Apoptosis In Myocytes and Cardiac Conduction Cellsmentioning
confidence: 99%
“…3 It has been reported that constitute 2% of all fetal arrhythmia, being 50% caused by congenital heart (left atrial isomerism, transposition of great arteries and endocardial), and 50% of immunologically associated with connective tissue diseases maternal. 1,4,5 Regarding immunological origin, this is caused by anti-Ro, and anti-LA maternal antibodies in 85-90%, and these antibodies expressed in collagen diseases such as systemic lupus erythematosus and Sjögren's síndrome. 6 A percentage of maternal carriers of anti-Ro and anti-La no symptoms of the disease, so there is a group of women who will be pregnant without knowing the risk to the fetus; 7 fortunately only about 2% of seropositive mothers fetuses present heart condition, particularly the piping system.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha reportado que los bloqueos AV constituyen el 2 % de todas las arritmias fetales, siendo el 50 % causadas por cardiopatías congénitas (isomerismo atrial izquierdo, transposición de grandes arterias y canal auriculoventricular), y el otro 50 % de origen inmunológico asociado a enfermedades de tejido conectivo materno (1,4,5). Respecto al origen inmunológico, este es causado por anticuerpos anti-Ro y anti-LA maternos en un 85-90 %, siendo estos anticuerpos expresados en enfermedades del colágeno como lupus eritematoso sistémico y síndrome de Sjögren (6).…”
Section: Introductionunclassified
“…La unión de inmunoglobulina tipo IgG a estos antígenos desencadena tres mecanismos patológicos: 1) mimetismo molecular (regulación a la baja de los canales tipo L y T, alteración de homeostasis de calcio intracelular); 2) inducción de apoptosis en miocitos y células de conducción cardiaca; 3) inducción de fibrosis (opsonización de cardiomiocitos y sistema de conducción) que genera eliminación de las células de conducción cardiaca, y produce inflamación y fibrosis, en especial del nodo sinoauricular (9). Los anticuerpos pueden ser transferidos en cualquier momento de la gestación (10), iniciando su paso placentario a las 12 semanas; el periodo de mayor vulnerabilidad oscila entre las 16 y 24 semanas, cuando suele haber un pico en la concentración de anticuerpos, lo que explica el hecho de que más del 80 % de los casos de bloqueo AV congénito sean diagnosticados antes de la semana 30 (4,10).…”
Section: Introductionunclassified
“…Among the conclusions from their data were the following statements: "the overall diagnostic performance of the IFA, EIA, and MIA were not statistically different...." Our primary focus will be on the above quoted words, with additional attention given to the propensity of HEp-2 cell lines to miss anti-Sjögren's Syndrome (SS)-A, which was also highlighted by Deng et To illustrate the "individuality" of ANA methods, we present 2 cases that we have encountered in our own laboratory practices. One of us has recently published a clinical case study primarily concerning the diagnosis of congenital heart block, where ANA HEp-2 by IFA failed at detecting anti-SS-A in the mother's serum (2). The other 2 of us have had a similar experience with a case of lupus rash reported by a neonatologist when questioning the disparity between the negative ANA on his patient and his clinical findings.…”
mentioning
confidence: 99%